Research ethics education in Korea for overcoming culture and value system differences - Hwan-jin Nho (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Although ethical standards and procedures for research in Korea have developed closer to global standards, applying those standards and procedures have led significant conflicts widely due to the cultural differences. In Korea where relationship-centered East Asian values are crucial, it is difficult for "internal whistleblowing" and "conflicts of interest management" to function properly. At universities, it is difficult to form an equal relationship to have a free discussion between professors and students. Also, the research community has been influenced by side effects such as "respect for quantity and speed", "excessive competition", and "mammonism" that have permeated Korean society during its modernization process. Students have taken such values for granted, too. These circumstances disable research ethics system to function properly and have negative influence on organization development by discouraging open innovation. In this context, how can we educate students to follow the global standards as well as dealing with conflicts derived from cultural differences wisely? I propose that the overarching principle of research ethics education should not be a "delivery of knowledge" but be a "change in the way of thinking". In this paper, five-stage education is proposed. As education methods, discussing of dilemma cases, avoiding remote online education and leading the whole team teaching classes by one head lecturer are recommended. In addition, classroom education should be provided together with social education to change the students' ways of thinking. As for social education, self-effort of universities and operational behaviour of research laboratories are two most important aspects. The government should establish legislation and expand financial support to facilitate these changes. It is very important that the universities should become key drivers that purify their member societies so that the nation may prosper.
Keywords: 650; Research ethics; Research ethics education; Scope of research ethics; Disparity in Korean society; Educational method